Multiplexing of unformatted asynchronous serial data to a single NMEA 0183 protocol compliance data-stream for autonomous surface vehicles data logging - Mat Idris, Mohamad Hilmi; Sahalan, Muhammad Irsyad; Abdullah , M. A.; Zainal Abidin, Zulkifli (Asian Research Publishing Network (ARPN), 2015)
Development of autonomous surface vehicle (ASV) for hydrography survey requires varieties of transducers to be setup. However, several of the commercial of the shelf (COTS) transducers are using a different format of data transmission. Therefore, there is a need for built-in communication protocols for seamless integration to your monitoring platform and data logging. This paper focuses on the practical implementation of the technique to convert unformatted asynchronous serial data from transducers into NMEA 0183 protocol. NMEA 0183 protocol is being selected as the common protocol since it is used by many marine vehicles. The technique lies on extracting the non-formatted asynchronous serial data and generates a custom made NMEA sentence that complies with the format. By implementing such technique, the data will not only synchronize in a single format but also stamp with the global positioning system (GPS) data which is crucial for mapping.